Roles of the Exosomes Derived From Myeloid-Derived Suppressor Cells in Tumor Immunity and Cancer Progression - Chen, Zhuang; Yuan, Rui; Hu, Shengyun; Yuan, Weitang; Sun, Zhenqiang (Frontiers in Immunology, 2022)
Tumor immunity is involved in malignant tumor progression. Myeloid-derived suppressor cells (MDSCs) play an irreplaceable role in tumor immunity. MDSCs are composed of immature myeloid cells and exhibit obvious immunomodulatory functions. Exosomes released by MDSCs (MDSC-Exos) have similar effects to parental MDSCs in regulating tumor immunity. In this review, we provided a comprehensive description of the characteristics, functions and mechanisms of exosomes. We analyzed the immunosuppressive, angiogenesis and metastatic effects of MDSC-Exos in different tumors through multiple perspectives. Immunotherapy targeting MDSC-Exos has demonstrated great potential in cancers and non-cancerous diseases.